Resection margins and local recurrences in breast cancer: Comparison between conventional and oncoplastic breast conserving surgery. Issue 6 (June 2019) - Niinikoski, Laura; Leidenius, Marjut H.K.; Vaara, Päivi; Voynov, Aleksandar; Heikkilä, Päivi; Mattson, Johanna; Meretoja, Tuomo J.
Abstract: Background: This retrospective cohort study aims to compare surgical margins, reoperations and local recurrences after conventional or oncoplastic breast conservation surgery (BCS). Furthermore, we aim to investigate differences between various oncoplastic techniques. Material and methods: We reviewed 1800 consecutive patients with primary invasive breast cancer (N = 1707) or ductal carcinoma in situ (N = 93) who underwent BCS at Helsinki University Hospital between 2010 and 2012. Results: Conventional BCS was performed in 1189 (66.1%) patients, oncoplastic BCS in 611 (33.9%). Various oncoplastic techniques were used. Patients with oncoplastic BCS had more often multifocal (p < 0.001), larger (p < 0.001), palpable tumours (p < 0.001) with larger resection specimens (p < 0.001). The amount of resected tissue varied substantially depending on the oncoplastic technique. Patients treated with oncoplastic BCS were younger (p < 0.001) and their tumours were more aggressive according to histological grade (p < 0.001), T-stage (p < 0.001), Ki-67 (p < 0.001) and lymph node status (p < 0.001). There was no difference, however, in surgical margins (p = 0.578) or reoperation rates (p = 0.430) between the groups. A total of 152 (8.4%) patients were reoperated because of insufficient margins, 96 (8.1%) in the conventional, 56 (9.2%) in the oncoplastic BCS group. The median follow-up time was 75 (2–94) months. There was no difference in local recurrence-free survival between the conventional and oncoplastic BCS groups (log-rank test, p = 0.172). Conclusions: Oncoplastic BCS was used for larger, multifocal and more aggressive tumours. Nevertheless, no difference in reoperation rate or local recurrences were found. Oncoplastic BCS is as safe as conventional BCS enabling breast conserving for patients who otherwise were candidates for mastectomy.